2020
DOI: 10.1002/jbmr.3982
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates Do Not Affect Bone Density or Bone Turnover in Postmenopausal Women: A Randomized Controlled Trial

Abstract: Organic nitrates have been reported to have significant effects on bone mineral density (BMD) and bone turnover in previous clinical trials. However, results are inconsistent and some trials with strikingly positive results have been retracted because of scientific misconduct. As preparation for a potential fracture prevention study, we set out to determine the lowest effective dose and the most effective and acceptable nitrate preparation. We undertook a 1‐year, double‐blind, randomized, placebo‐controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The results of four randomized controlled trials on the effects of nitrates on BMD were inconsistent. There were no statistically significant differences in BMD percent change at any sites in these two RCTs compared with a placebo ( 14 , 15 ). In contrast, nitrates and alendronate had similar effects in increasing bone BMD in another two RCTs ( 16 , 25 ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The results of four randomized controlled trials on the effects of nitrates on BMD were inconsistent. There were no statistically significant differences in BMD percent change at any sites in these two RCTs compared with a placebo ( 14 , 15 ). In contrast, nitrates and alendronate had similar effects in increasing bone BMD in another two RCTs ( 16 , 25 ).…”
Section: Discussionmentioning
confidence: 73%
“…However, one cohort study found no evidence that nitrate use was related to a decreased incidence of fractures or a higher BMD (13). Furthermore, the results of two randomized controlled trials (RCTs) that examined the effects of nitroglycerin ointment on BMD were contradictory (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…According to a meta‐analysis of the prospective cohort, cross‐sectional, and clinical trial studies, the Mediterranean diet, a rich source of inorganic nitrate, has body weight‐lowering effects and decreases the risk of obesity‐related diseases in humans 34 . In contrast, organic nitrates are poorly tolerated, 35,36 increase body weight, 37 and induce tachyphylaxis following chronic use 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…10 According to a meta-analysis of the prospective cohort, cross-sectional, and clinical trial studies, the Mediterranean diet, a rich source of inorganic nitrate, has body weight-lowering effects and decreases the risk of obesity-related diseases in humans. 34 In contrast, organic nitrates are poorly tolerated, 35,36 increase body weight, 37 and induce tachyphylaxis following chronic use. 38,39 Our result showed that nitrate administration to female rats increased serum NO x levels, which was positively correlated with serum progesterone but not 17β-estradiol levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study of 240 postmenopausal women with low bone densities, no significant BMD change was noted. Of note, the withdrawal rate was quite high (∼20%) in the active treatment arm mainly due to headaches 50 …”
Section: No Donors and Bonementioning
confidence: 97%